Estação meteorológica portátil com cultura maker interdisciplinar para ensino de física e programação de computadores - Melo, Larissa Alencar de (2021)
It is known that teaching physics can be considered difficult due to so many calculations, graphs and numbers. Often, the ability to associate formulas and theoretical content with everyday life does not happen clearly for students. In addition, teaching Computer Programming is also difficult for students, as they often lack the skills to understand the logical steps for solving problems using a computer. Therefore, the objective of the project presented in this article is to facilitate the teaching of Physics through the maker culture, in the do-it-yourself (DIY) process. As a case study to apply the maker culture to the teaching of Physics and Computer Programming, we created a portable meteorological station with Arduino, a low cost free hardware, so that students could relate Thermodynamics to Computer Programming, in this way seeking to improve the way of reasoning and visibility with the help of theoretical Physics, maker culture and everyday life. In the construction of this meteorological station, it was possible to study and visualize the state variables of Thermodynamics using Arduino as a monitoring platform. In our work, we were initially going to perform experiments in person, but we had to apply remote experiments due to the covid-19 pandemic. In this experiment, 20 second-year High School students of a technical course in Electronics participated from a science and technology institution in Brazil. All students were subjected to an initial test regarding concepts of Thermodynamics and Computer Programming, in order to obtain the initial diagnosis of these students. Then, all the students attended an online lesson from the Physics teacher and finally, the students were divided, through a draw, into 2 groups: the group that participated in the remote maker experiments (10 students) and the group that did not participate (10 students). We applied a final test to the whole class, in order to obtain the levels of expertise of the class regarding the concepts of Thermodynamics and Computer Programming. The results obtained, the comparison between the groups that participated and did not participate in the remote maker activities, the report of these remote experiences and the adjustments made to reach the largest possible number of students show the feasibility of the proposal, in addition to reported challenges and future directions.